Biodiversity of Birds in Urban Green Space for Support Ecotourism activities in Valaya Alongkorn Rajabhat University Thailand - BORUAH, Ichangdaw; HASIN, Sasitorn; POPRADIT, Ananya; SAWASDEE, Vanatpornratt; CHEENTAM, SOONTAREE (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).25, 2021)
Bird watching is one of the attractive ecotourism activities for travelers and nature enthusiasts, which rapidly growing in Thailand. This study aims to: (1) explore bird diversity in various green spaces in ValayaAlongkorn Rajabhat University (VRU); and (2) examine which bird species dominates the study areas. Bird data were collected using point count techniques in two sessions; early morning, and late afternoon, at VRU from May 2020 to April 2021. Frequency of occurrence value (FQ) was analyzed for classifying status groups of birds in the VRU. Order Passeriformes was numerically the dominant order in our study area, with 22 species (47.7% of total represented species), while the other bird orders were the least dominant, represented by 1 to 5 species in range. A total of 47 species of birds belonging to 29 Families and 12 Orders were recorded. During this study, significantly, the highest bird richness was recorded in agriculture areas (35 ± 2.3 SD), followed by the species from recreation areas (27 ± 1.8 SD) and natural wetland (17 ± 1.7 SD) (P>0.05). Five migrant bird species and 35 resident species were observed, and 10 bird species were recorded in both the seasonal status as migrant and resident species. Most of the bird species are listed as of least concern, while only one species, Mycteria leucocephala , are listed as near-threatened. Nine bird species are classified as common species in the VRU with > 80 % of frequency of occurrence. The pattern of bird diversity in the VRU in general follows the natural condition of green area space in the VRU. Typical characteristics of birds, their habitat and appearing period can develop bird-watching objects, which become interesting attractions for travelers and nature enthusiasts, promoting ecotourism development and efforts to conserve bird diversity.